The Effect of Investment and Labor on Economic Growth in West Sulawesi Province - Aswar Rahmat*; Taufik Hidayat B Tahawa; Awal Nopriyanto Bahasoan (Universitas Syiah Kuala, 2023)
This article discusses the effect of investment and labor on economic growth in West Sulawesi Province. West Sulawesi Province is one of the regions in Indonesia which has considerable economic potential. Investment and labor are two important factors in driving economic growth in a region. In this article, we will discuss the role of investment and labor and their impact on economic growth in West Sulawesi Province.